PENGARUH PENERAPAN EXPERIENTIAL MARKETING TERHADAP KEPUASAN KONSUMEN PADA PT. PUTRA ALI SENTOSA (PAS) PONDOK BATU KABUPATEN TAPANULI TENGAH - Rinto Siahaan; Mansur Tanjung; Sriayu Aritha Panggabean (KOLONI, 2023)
This study aims to determine whether there is/is not the influence of the application of experiential marketing on consumer satisfaction at PT. Putra Ali Sentosa (PAS) Pondok Batu, Central Tapanuli Regency. This research uses a type of quantitative descriptive research because this research method has the aim of obtaining information by making a picture or description of what is or is happening. The type of data used in completing this thesis research proposal is subject data (Self-report data). The source of the data collected is in the form of primary data which is obtained directly from the respondents who are the target of the research. The results obtained between the variables X and Y for each item are declared valid and reliable because the total value of the corrected item is greater than the critical r value (0.30) and the Cronbach Alpha value is above 0.60. From the normality test, all show that the distribution of the data does not violate the normality assumption, namely in the form of a bell and the data distribution is close to the diagonal line in the normal curve of the P-P Plot and the non-paramertic solid table sig value is greater than 0.05 so that for the Experiential Marketing variable and consumer satisfaction it can be concluded normal. There is a positive relationship between Experential Marketing and consumer satisfaction which can be proven through the calculation of the correlation coefficient with a strong correlation result of = 0.737. From the calculation of the coefficient of determination, it is obtained a figure of 54.4%, this means that what occurs in the variation of the dependent variable (customer satisfaction) of 45.6% is determined by the independent variable (Experential Marketing) and the remaining 40.1% is determined by other variables. not discussed in this study, such as service quality variables, marketing mix, distribution and others. From the hypothesis testing carried out and by comparing the calculated t value with the t table value, it is found that the t calculated value is greater than t table (6.729 > 2.024). This means that the accepted hypothesis is the alternative hypothesis (Ha). Keywords: Experiential Marketing and Consumer Satisfaction